2013
DOI: 10.1155/2013/308204
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Safety of Blood Collected for Transfusion at University of Gondar Hospital Blood Bank, Northwest Ethiopia

Abstract: Background. Transfusion associated bacterial infection has remained more frequent with a sever risk of morbidity and mortality. This study assessed the bacteriological safety of blood collected for transfusion. Method. A cross-sectional study was conducted at University of Gondar hospital blood bank from December 2011 to June 2012. Bacterial isolation, identification, and antimicrobial susceptibility tests were done as per the standard procedure. Chi-square test and P value were used to assess associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 25 publications
3
15
3
Order By: Relevance
“…In the study, the prevalence of bacterial contamination of blood and blood component was 9.2%. The bacterial contamination on this study is lower than other similar studies done in Gondar and Debre Markos [19, 20], Ghana; 17.5% [17] and Egypt 17.9% [25]. However, result of this study is relatively higher than study conducted in America; 0.2% [10], UK; 0.15%, [11], France; 0.1 [12], Zimbabwe; 3.1% [26], Uganda; 3.5% [27].…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…In the study, the prevalence of bacterial contamination of blood and blood component was 9.2%. The bacterial contamination on this study is lower than other similar studies done in Gondar and Debre Markos [19, 20], Ghana; 17.5% [17] and Egypt 17.9% [25]. However, result of this study is relatively higher than study conducted in America; 0.2% [10], UK; 0.15%, [11], France; 0.1 [12], Zimbabwe; 3.1% [26], Uganda; 3.5% [27].…”
Section: Resultscontrasting
confidence: 61%
“…Other studies from sub-Saharan African countries showed that the prevalence of contamination of donated blood is higher than that of developed countries [1419]. Except few studies done in Gonder and Debre Markos [20, 21], bacterial contamination of donated blood in Ethiopia has not been given due attention unlike that of transfusion-transmitted viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…Data from published studies have reported a high risk of transfusion-associated bacterial contamination; for example, a study conducted among 80 refrigerated blood units in Ghana found a 17.5% contamination with bacteria 15. In Ethiopia, bacterial contamination was reported at 15.33% and 12.5%,16,17 and 3.5% in Mbarara Regional Blood Bank, Uganda 3. These studies affirm a high burden and risk of unsafe donor blood; however, there are no novel approaches and improvements in the existing practices to limit and avert the associated risk in developing settings.…”
Section: Introductionmentioning
confidence: 92%
“…Some staff members may not wear or change gloves 23 between patients, either because of limited supply or lack of training and supervision. In some cases, staff members have expressed concern that they would not be able to feel a vein with gloves on.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, staff members have expressed concern that they would not be able to feel a vein with gloves on. Touching the incision site to find the vein after alcohol swabbing is common 23 and can expose the patient to risk of infection.…”
Section: Introductionmentioning
confidence: 99%